Islotes Farallones de Carelmapu: sitio de alto valor para la reproducción de aves marinas en el sur de Chile (Revista de Biología Marina y Oceanografía, 2024)
The Peruvian Booby (Sula variegata) and the Peruvian Pelican (Pelecanus thagus) are endemic seabirds from the Humboldt Current System. This work aimed to evaluate the conservation value of the Farallones de Carelmapu and its use as a nesting site for seabirds. The information obtained shows the southernmost breeding record of the Peruvian Booby and the Peruvian Pelican, in the Farallones de Carelmapu (41°S), located on the coast of Maullín, southern Chile. On February 12, 2022, 29 active Peruvian Booby nests were recorded; for the Peruvian Pelican, 114 chicks and 39 fledglings were estimated. In addition, the Farallones de Carelmapu are described for the first time as an important breeding site for the seabirds and very relevant for the creation of a new marine protected area.